2020
DOI: 10.1111/bph.14864
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine differentially modulates coronary vasodilation in control and diabetic mice

Abstract: Background and Purpose: Chloroquine is a traditional medicine to treat malaria.There is increasing evidence that chloroquine not only induces phagocytosis but regulates vascular tone. Few reports investigating the effect of chloroquine on vascular responsiveness of coronary arteries have been made. In this study, we examined how chloroquine affected endothelium-dependent relaxation in coronary arteries under normal and diabetic conditions. Experimental Approach: We isolated coronary arteries from mice and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Chloroquine has been shown to differentially modulate coronary arterial vasodilation in diabetic mice [8]. In humans, it decreases nitric oxide production in coronary artery endothelial cells.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Chloroquine has been shown to differentially modulate coronary arterial vasodilation in diabetic mice [8]. In humans, it decreases nitric oxide production in coronary artery endothelial cells.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…In the presence of CQ, the reduced ATP synthesis and release from RBCs leads to a decrease in NO synthesis and diffusion, which in turn negatively affects vasodilation input. This hypothesis is partly confirmed by Perecko et al who showed that both chloroquine and its hydroxyderivative, hydroxychloroquine, inhibited NO production in the immortalized mouse macrophage cell line RAW 264.7 and mouse bone marrow-derived macrophages [ 51 , 52 ]. The above reports open new points of research on the side effects of the drug, especially in patients with coronary or cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 72%
“…CQ/HCQ effects differ between normal and diseased cardiovascular systems. In a murine model, CQ inhibited endothelial-dependent coronary vascular relaxation in control mice but increased it in diabetic TALLYHO/Jng mice ( 97 ), underscoring the special link between CQ/HCQ and type 2 diabetes which will be detailed below.…”
Section: Effects Of Cq/hcq On Non-immunological Cell Typesmentioning
confidence: 89%
“…Finally, as a broad-spectrum agonist of TAS2R, CQ increases the intracellular concentration of Ca 2+ in airway smooth muscle cells through PLCβ (Phospholipase Lipase C β) activation, inositol-trisphosphate (IP3) production and binding to endoplasmic reticulum IP3 receptor, followed by the mobilization of Ca 2+ stores ( 53 ). As a result, CQ administration results in airway smooth muscle relaxation, even in precontracted airways, thus reversing airway obstruction in human, murine, and guinea pig models ( 97 ).…”
Section: Effects Of Cq/hcq On Non-immunological Cell Typesmentioning
confidence: 99%